Measuring the Performance of Maintenance Service Outsourcing (2013)
The aims of this paper are (1) to identify the characteristics of maintenance service providers that directly impact maintenance service quality, using 18 independent covariables; (2) to quantify the change in risk these covariables present to service quality, measured in terms of equipment turnaround time (TAT). A survey was applied to every maintenance service provider (n = 19) for characterization purposes. The equipment inventory was characterized, and the TAT variable recorded and monitored for every work order of each service provider (N = 1,025). Finally, the research team conducted a statistical analysis to accomplish the research objectives. The results of this study offer strong empirical evidence that the most influential variables affecting the quality of maintenance service performance are the following: type of maintenance, availability of spare parts in the country, user training, technological complexity of the equipment, distance between the company and the hospital, and the number of maintenance visits performed by the company. The strength of the results obtained by the Cox model built are supported by the measure of the R2p,e = 0.57 with a value of R p,e= 0.75. Thus, the model explained 57% of the variation in equipment TAT, with moderate high positive correlation between the dependent variable (TAT) and independent variables. © Copyright AAMI 2013.